Pengaruh Adat Lunang Baduy Dalam dan Adat Lunang Baduy Luar Terhadap Keputusan Memilih Presiden dan Wakil Presiden pada Pemilu 2024 - Suryaningsih Suryaningsih; Muhammad Hendri Nuryadi; Rima Vien Permata (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to determine the influence of the Lunang custom adopted by the Inner Baduy and Outer Baduy communities on the decision to elect the President and Vice President in the 2024 General Election. This study uses a descriptive quantitative method involving 140 respondents from the Baduy community in Kanekes Village, Lebak Regency, Banten Province. Data collection was conducted through questionnaires, then analyzed using descriptive statistics to determine trends and patterns of political decision-making. The results show that the Inner Baduy community tends to be politically neutral based on customary law and spiritual beliefs that emphasize separation from external political affairs. In contrast, the Outer Baduy community shows selective participation influenced by the process of cultural adaptation to the outside world. This study concludes that differences in interpretation and application of the Lunang custom between the two communities have a significant influence on their political decisions, reflecting the role of customary values ​​in shaping democratic participation in Indonesia.